EPIDEMIOLOGICAL PECULIARIETIES HYPERTENSIVE ENCEPHALOPATHY AT PAТIENTS POLTAVA REGION WICH LITES IN VILLAGE - Lytvynenko, N.V.; Кривчун, А.М. (World of Medicine and Biology, 2010)
In article explain epidemiological peculiarieties of arterial hypertensive and hypertensive dyscirculative encephalopathy amoung the people which lites in village Poltava region. Constant, that guantaly arterial hypertension was 47,6%. Amoung 409 hypertensive patients at 20% people diagnostic pathology of nervosus system hypertensive dyscirculative encephalopathy was diagnostic at 78% ( I degree – at 26%, II – at 49%, IIІ– 3% patients). Degree of pathological changes in nervosus system correlated with disturbances lipids.